Cashew nut (Anacardium occidentale L.) and cashew nut oil reduce cardiovascular risk factors in adults on weight-loss treatment: a randomized controlled three-arm trial (Brazilian Nuts Study) - Meneguelli, Talitha Silva; Kravchychyn, Ana Claudia Pelissari; Wendling, Aline Lage; Dionísio, Ana Paula; Bressan, Josefina; Martino, Hercia Stampini Duarte; Tako, Elad; Hermsdorff, Helen Hermana Miranda (Frontiers in Nutrition, 2024)
Introduction Cashew nut contains bioactive compounds that modulate satiety and food intake, but its effects on body fat during energy restriction remains unknown. This study aimed to assess the effects of cashew nut and cashew nut oil on body fat (primary outcome) as well as adiposity, cardiometabolic and liver function markers (secondary outcomes). Materials and methods An eight-week (8-wk) randomized controlled-feeding study involved 68 adults with overweight/obesity (40 women, BMI: 33 ± 4 kg/m2). Participants were randomly assigned to one of the energy-restricted (−500 kcal/d) groups: control (CT, free-nuts), cashew nut (CN, 30 g/d), or cashew nut oil (OL, 30 mL/d). Body weight, body composition, and blood collection were assessed at the baseline and endpoint of the study. Results After 8-wk, all groups reduced significantly body fat (CT: −3.1 ± 2.8 kg; CN: −3.3 ± 2.7 kg; OL: −1.8 ± 2.6 kg), body weight (CT: −4.2 ± 3.8 kg; CN: −3.9 ± 3.1 kg; OL: −3.4 ± 2.4 kg), waist (CT: −5.1 ± 4.6 cm; CN: −3.9 ± 3.9 cm; OL: −3.7 ± 5.3 cm) and hip circumferences (CT: −2.9 ± 3.0 cm; CN: −2.7 ± 3.1 cm; OL: −2.9 ± 2.3 cm). CN-group reduced liver enzymes (AST: −3.1 ± 5.3 U/L; ALT: −6.0 ± 9.9 U/L), while the OL-group reduced LDL-c (−11.5 ± 21.8 mg/dL) and atherogenic index (−0.2 ± 0.5). Both intervention groups decreased neck circumference (CN: −1.0 ± 1.2 cm; OL: −0.5 ± 1.2 cm) and apo B (CN: −6.6 ± 10.7 mg/dL; OL: −7.0 ± 15.3 mg/dL). Conclusion After an 8-wk energy-restricted intervention, all groups reduced body fat (kg), weight, and some others adiposity indicators, with no different effect of cashew nut or cashew nut oil. However, participants in the intervention groups experienced additional reductions in atherogenic marker, liver function biomarkers, and cardiovascular risk factors (neck circumference and apo B levels), with these effects observed across the OL group, CN group, and both intervention groups, respectively. Clinical trial registration:https://ensaiosclinicos.gov.br/rg/RBR-8xzkyp2, identifier 8xzkyp2.